2016 European guideline for the management of vulval conditions. (6th February 2017) - van der Meijden, W.I.; Boffa, M.J.; ter Harmsel, W.A.; Kirtschig, G.; Lewis, F.M.; Moyal‐Barracco, M.; Tiplica, G.S.; Sherrard, J.
Abstract: Vulval conditions may present to a variety of clinicians, such as dermatologists, gynaecologists and general practitioners. Women with these conditions are best managed by a multidisciplinary approach, which includes clear referral pathways between disciplines or access to a specialist multidisciplinary vulval service. Informed consent is a prerequisite for all examinations, investigations and treatments. Consent is particularly important for intimate examinations of the anogenital area, and a chaperone should be offered in all cases. All efforts should be made to maintain a patient's dignity. Depending on symptoms and risk factors, screening for sexually transmitted infections (STI) should be considered. If the patient presents with vulval itch, particularly if also complaining of increased vaginal discharge, vulvaginal candidiasis should be excluded. Sexual dysfunction should be considered in all patients with vulval complaints, either as the cause of the symptoms or secondary to symptoms, and assessed if appropriate. This guideline covers several aspects, such as diagnosis and treatment, of the more common vulval conditions (relatively) often encountered at vulval clinics, i.e. vulval dermatitis (eczema), psoriasis, lichen simplex chronicus, lichen sclerosus, lichen planus, vulvodynia and vulval intraepithelial neoplasia (VIN).